Essays on asset pricing: comparisons of factor models, investigations of the roles of illiquidity, R&D investment, product market competition, and labor mobility - Bu, Ziwen (2019)
This thesis comprises three essays in asset pricing, with a focus on scrutinizing factor models and dissecting anomalies. In the first chapter, I compare major factor models and find that the Stambaugh and Yuan (2016) four-factor model is the overall winner in the time-series domain. The Hou, Xue, and Zhang (2015) q-factor model takes second place and the Fama and French (2015) five-factor model and the Barillas and Shanken (2018) six-factor model jointly take third place. But the pairwise cross-sectional R^2 and the multiple model comparison tests show that the Hou, Xue, and Zhang (2015) q-factor model, the Fama and French (2015) five-factor and four-factor models, and the Barillas and Shanken (2018) six-factor model take equal first place in the horse race.